Islamic Dialectics and Local Cultural Transformation in the Matajang Community, Enrekang Regency - Bahri, Syamsul; Iskandar, Abdul Malik; Harifuddin, Harifuddin; Azuz, Faidah; Madiong, Baso; Waspada, Waspada (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
This article aims to (i) describe the dialectic of Islam with local culture in the Matajang community. (2) describe the form of local cultural transformation as a result of dialectics with Islam in the Matajang community. This research is qualitative with a single case study design. The research locations are in the Matajang community which includes Labuku Village, Baringeng Village, and Tapong Village and Matakali Village. The research informants consisted of 4 traditional leaders. Data collection used in-depth interviews, observation, and literature studies. Data analysis uses a three-plot technique, namely data reduction, categorization. The results of this study are (1) the dialectic of Islam and local culture has a meeting point in the occult aspect. Both acknowledge the existence of the supernatural and it is in this aspect that Islam is accepted by the Matajang people. (2) The transformation of local ritual culture occurs in several rituals gradually, starting from changes in prayers and matra to changes in some parts of the ritual but the local aspects are still visible. The conclusion of cultural change is a form of negotiating Islamic culture with local culture because not all forms are taken, only those that are appropriate to local characteristics.